Impaired Function of Regulatory T Cells in Type 2 Diabetes Mellitus - Rona Kartika; Heri Wibowo (Cell and BioPharmaceutical Institute, 2020)
Pathogenesis of type 2 Diabetes Mellitus (DM) is often associated with chronic low-grade inflammation. This kind of inflammation is characterized by an increased level of pro-inflammatory cytokines such as tumor necrosis factor α (TNF-α), interleukin (IL)-6 and IL-1β. From an immunological point of view, an inflammatory response is always followed by an anti-inflammatory response as negative feedback to avoid excessive tissue damages. Regulatory T cells are a subset of cluster of differentiation (CD)4+ T cells that have the function to maintain peripheral tolerance and suppress immune response. This review would discuss the impaired function of regulatory T cells in type 2 DM. DM is a group of metabolic diseases characterized by hyperglycemia due to a defect of insulin secretion or a combination of insulin resistance and relative insulin deficiency. Chronic low-grade inflammation has been known as a key factor in the development of insulin resistance. Regulatory T cells (Treg cells) action through contact and non-contact inhibition could suppress inflammatory response in innate and adaptive immune systems. In type 2 DM, the proportion and function of CD4+CD25+Foxp3+ and CD4+CD25+ regulatory T cell decreases due to the reduced number of Treg cells and the Treg cells depletion contributes to metabolic conditions such as insulin resistance. Moreover, Treg cells are more susceptible to apoptosis, the ability of Treg cells to produce anti-inflammatory cytokines such as transforming growth factor β (TGF-β) and IL-10 decreases, and there is an imbalance between the proportion of Th1/Th17 cells and Treg cells. This inadequate anti-inflammatory response gives rise to the chronic low-grade inflammatory condition in type 2 DM.Keywords: type 2 diabetes mellitus, inflammation, regulatory T cell